Measuring Inequality in the Polish Income Tax System - Kośny, Marek; Mazurek, Edyta (Pomiar nierówności w polskim podatku dochodowym od osób fizycznych, 2009)
In this paper the equity in income taxation is defined by means of three axioms, introduced by Kakwani and Lambert in 1998. Tax system is equitable if all axioms are satisfied. Violation of them - by a personal income tax system - produces negative influence on the redistributive effect of the tax. This negative influence provides the means to characterize the type of inequity present in a tax system. We analyze these effects, using decomposition of the redistributive effect. The analysis is made basing on data from the tax offices and household budget survey.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 66, s. 83-91